Development of a comprehensive method for musculoskeletal simulation in swimming using motion capture data - Nakashima, M.; Kanie, R.; Shimana, T.; Matsuda, Y.; Kubo, Y. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2023)
The objective of this study was to develop a comprehensive method for musculoskeletal simulation in swimming. In the developed method, the motion capture data of a swimming motion were first transformed into input data for the swimming human simulation model Swimming Human Model (SWUM). Then, the output data from SWUM were transformed into input data for the musculoskeletal simulation. In order to examine the validity of the developed method, the musculoskeletal simulations of the crawl and breaststroke by two swimmers were conducted. Based on the results of the crawl, the muscles of the upper limbs were activated significantly at the pull and push phases. The swimmer also adjusted the swimming speed, not by changing the effort of the upper limbs during the pull and push phases but by changing the length of the entry phase and the effort of the flutter kick. The results of the breaststroke showed that the muscles of the lower limbs were activated significantly at the kick phase. The swimmer adjusted the swimming speed, not by changing the effort of the upper limbs but by changing the length of the glide phase and the effort of kicking. The results from this study were consistent with the findings in previous studies, except for the period of large (nearly 180 degrees) flexion or abduction at the shoulder joint. The results also revealed the strategies of the swimmers to adjust their swimming speed. This indicates the promising potential of the musculoskeletal simulation, that is, it will be possible to estimate the strategy of a swimmer by conducting the simulation.